Deformation and Failure Mode Analysis of the Tunnel Structure Based on the Tunnel-Related Landslides Cases - Minglei, Sun; Hongwei, Liang; Yongquan, Zhu; Xinqiang, Gao; Huan, Liu; Zhengguo, Zhu (Frontiers in Earth Science, 2022)
When the tunnel passes through the slope area, once the slope stability changes or landslide disasters occur, large additional stress, deformation, or cracking are easily caused in the tunnel, which results in high risk to the tunnel operation. The deformation and failure mode of the tunnel induced by different types of tunnel-related landslides are different. However, there is no systematic classification of tunnel structure deformation and the failure mode in the tunnel-related landslides systems. By investigating the typical cases of tunnel diseases caused by landslide in China, this study analyzes the relationship between the tunnel-related landslide types and tunnel disease characteristics. It also summarizes five typical tunnel deformation failure modes and corresponding deformation characteristics and determines the relationship between tunnel-related landslide types and deformation failure modes. This study can provide a technical support for the identification of landslide types through the tunnel deformation characteristics in practical engineering applications. Finally, it provides a reference for tunnel location selection, the design of tunnel structure, and the treatment of landslide in landslide areas.